The meaning of recreational sports for modern society as a lifestyle to stay active and fit - Cahyo Wibowo; Sanfia Tesabela Messakh; Rival Aruna Tarigan (Universitas Riau, 2023)
(English)This research explores the meaning of recreational sports for modern society as a lifestyle to stay active and fit. This qualitative research uses a phenomenological approach in Salatiga City in several open and closed sports venues and open sports facilities provided by the city government. The population is an urban community that does recreational sports. Random sampling in this study totaled twenty-five respondents from various sports community groups and individually. Data collection techniques used in-depth interviews. The data analysis technique uses the method from Milles and Huberman, which is divided into four stages: data collection, data reduction, data presentation, and conclusion. The results found are that modern society does not know the definition of recreational sports well; they do recreational sports in their free time to maintain fitness, recreational sports are used as a lifestyle with the family, and the environment and mass media are supporting factors in understanding and accessibility in doing recreational sports. This research concludes that modern society needs to understand recreational sports better. However, they consciously do it with internal motivation and support from the environment, including family and mass media.(Indonesian)Penelitian ini bertujuan untuk menggali makna olahraga rekreasi bagi masyarakat modern sebagai gaya hidup untuk tetap aktif dan bugar. Penelitian ini merupakan penelitian kualitatif dengan pendekatan fenomenologi dilakukan di Kota Salatiga di beberapa tempat olahraga terbuka dan tertutup juga di fasilitas olahraga terbuka yang disediakan oleh pemerintah kota. Partisipan merupakan masyarakat Kota Salatiga yang melakukan olahraga rekreasi. Partisipan yang diambil dalam penelitian ini berjumlah total dua puluh lima responden dari berbagai kelompok komunitas olahraga maupun secara individu. Teknik pengumpulan data menggunakan in-dept interview. Teknik analisis data menggunakan metode dari Milles dan Huberman yang dibagi menjadi 4 tahapan yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil yang ditemukan adalah masyarakat modern belum mengetahui definisi olahraga rekreasi dengan baik, mereka melalukan olahraga rekreasi di waktu luang untuk menjaga kebugaran, olahraga rekreasi dijadikan gaya hidup bersama keluarga, lingkungan dan media masa menjadi faktor pendukung dalam pemahaman dan aksesibilitas dalam melakukan olahraga rekreasi. Kesimpulan penelitian ini adalah masyarakat modern belum memaknai dengan baik olahraga rekreasi, namun secara sadar mereka melakukannya dengan motivasi internal dan juga dukungan dari lingkungan termasuk keluarga dan media masa. Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.